Enhancing academic performance of basic technology students through differentiated instruction strategies in Junior Secondary Schools - Olabiyi, Oladiran Stephen (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
This study investigated the improvement of basic technology students' achievement using differentiated instruction learning strategies in Nigerian junior secondary schools using a pre-test and post-test non-equivalent control group quasi-experimental design. The study was guided by three null hypotheses and three research questions, with the experimental group receiving tutelage using the differentiated learning strategy and the control group receiving instruction using the conventional teaching method for eight weeks. The Basic Technology Achievement Test (BTAT), with a KR-20 reliability coefficient of 0.85, was used to collect data. The findings revealed that students in the experimental group performed significantly better in basic technology than students in the control group. Furthermore, male students outperformed their female counterparts in basic technology with a differentiated learning strategy, though there was no significant difference between genders taught basic technology with a differentiated learning strategy. Gender had no statistically significant impact on students' achievement in woodworking technology. Furthermore, the interaction effect of treatment and gender on students' basic technology achievement was not statistically significant. The differentiated learning strategy made lessons more interesting and simpler, and it helped students form friendships. It was thus suggested that differentiated learning strategies be used as a close substitute for traditional teaching methods in teaching basic technology in Nigerian junior secondary schools.